Magnetic resonance imaging for noninvasive assessment of renal fat deposition and hypoxia in diabetic kidney disease - Jian Liu; Daoyu Yang; Chong Tian; Rui Lv; Rongpin Wang; Xianchun Zeng (BMC Medical Imaging)
Abstract Background Renal ectopic fat deposition and hypoxia are linked to renal function damage, but regional differences within the kidney and the relationship between renal fat deposition and abnormal oxygen metabolism remain unclear. Purpose To investigate the regional characteristics of the kidney and the interaction between abnormal renal fat deposition and oxygen metabolism in type 2 diabetes mellitus (T2DM). Methods A total of 26 healthy participants and 105 patients with T2DM underwent Dixon scan to quantify renal cortex and medulla proton-density fat fraction (PDFF) and relaxation rate (R2*). Patients with T2DM were classified into three groups by estimated glomerular filtration rate (eGFR). Differences in PDFF and R2* between groups and across renal compartments were analyzed using One-way ANOVA. Pearson’s correlation analysis assessed variable relationships, and receiver-operating-characteristic curve evaluated diagnostic performance. Results R2* values in the medulla were significantly higher than those for the cortex. Both PDFF and R2* values in the renal cortex and medulla differed significantly across the four groups, showing an increasing trend with disease severity: control group < T2DM < diabetic kidney disease (DKD) stage I-II < DKD stage III-IV. PDFF and R2* values exhibited a significant positive correlation. Renal medulla PDFF value demonstrated the best diagnostic performance in distinguishing: (1) T2DM patients without DKD from healthy controls (2), T2DM without DKD from those with DKD stage I-II, and (3) DKD stage I-II from DKD stage III-IV. Conclusions Generally, the renal medulla is more vulnerable to hypoxic injury, and disruptions in renal oxygen metabolism closely linked ectopic fat deposition. Quantitative MRI offers a promising approach for early detection and monitoring of diabetes-related renal damage.